The psychological impact of COVID-19 on healthcare work force in the Middle East region C-S study - El-Gammal, Marwa Ahmed; Elgendy, Amira; Heidler, Petra; Owais, Tarek A.; Eltewacy, Nael Kamel; Hamza, Nouran, the EARG group; Amir Rais, Mohammed; Ashraf, Reman; kamal abdou, Entesar; Sobhy Kiddees, Ereen; Abdelrazek Abdellah, Arwa; et al. (Frontiers in Psychiatry, 2023)
Introduction SARS corona virus-2, known as COVID-19, is one of the biggest challenges facing humanity in the 21st century (1). The pandemic outbreak as affected all human activities, starting with healthcare and medical service passing with economy and social relationships, as well as political, religious and cultural enactments (2). The healthcare workers were the most affected fighting in the frontline working longer hours under a high risk of being infected (3). They were saving lives and facing enormous physical and psychological pressure, working hard and being socially isolated from their families and friends (4). Globally health care workers were experiencing anxiety, depression, exhaustion, Post-traumatic stress disorder (PTSD), stress and mental health issues (5, 6). This study aims to assess the depression, anxiety and stress levels of the healthcare workforce (physicians, nurses, pharmacists and dentists) in the Middle East and North Africa – MENA – region. This region is facing poverty, deficiency on the personal protective equipment (PPE) and civil wars. According to the UN Syria is one of the countries that are undergoing “the largest humanitarian crisis since the second world war” ( , 7) and Yemen where it’s crisis was described by the UN in 2017 as the worst humanitarian crisis since 1945 (8). In addition, war, riots and terrorism complicate the situation in Libya, Palestine, South Sudan, Ethiopia, Central African Republic, Mali, Niger, Burkina Faso and Cameroon. Our investigation includes 11 countries from the MENA region (Egypt, Algeria, Iraq, Jordon, Libya, Palestine, Saudi Arabia, Sudan, Syria, Tunisia and Yemen) using the depression anxiety stress scale (DASS-21). In addition, our study aimed to assess the psychological effect of COVID-19 infection on the mental health of individuals by calculating the odds ratio of the psychological state of those who were infected with COVID-19 to that of others who did not have the disease. Moreover, the study aimed to assess the effect of the vaccines on the mental health of the individuals through the same criteria.